Development of English Writing Skills through Short Stories for Students of Class XI SMA N Amanuban Timur, Kab. Timor Tengah Selatan, NTT - Isu, Rudolof Jibrael; Selan, David R. E.; Bessie, Delorens Lorentje Naomi; Boimau, Sanhedri; Manek, Agnes O.; Ndun, Yandri S.; Selan, Yacob A. N.; Langkameng, Oce A.; Malelak, Deby M. (Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to develop English writing skills through the use of short stories for grade XI students of SMA N Amanuban Timur. Writing in English is an important skill that students must master, both for academic purposes and daily life. However, many students face difficulties in organizing ideas in a structured manner and mastering the use of appropriate vocabulary and grammar. Therefore, the use of short stories as a learning method is an effective and interesting solution to improve writing skills. This method involves several stages, starting from analyzing the structure of short stories, selecting themes that match students' interests, to the process of writing stories. In addition, peer review or peer feedback sessions are conducted to provide constructive feedback, which allows students to improve and develop their writing. The results of this study showed that the short story approach successfully improved students' writing skills, enriched their vocabulary, and increased their confidence in speaking and writing in English. Thus, this method can be an effective alternative in learning English at the high school level.